G527(P) The incidence of paediatric cystic fibrosis admissions in Irish public hospitals; 2009–2013 – An analysis of admission diagnoses and mortality. (27th April 2016) - McCarthy, KN
Abstract : Aims: Cystic Fibrosis is the most commonly occuring life limiting inherited disease in Ireland with an incidence of 1 in 1461. We sought to evaluate trends in paediatric and adult hospital admissions for patients with any listed diagnosis of CF using the Hospital In-Patient Enquiry system data. Methods: The HIPE system was evaluated from 57 hospitals from 2009–2013 for patients with any listed diagnosis of CF. Data recorded included diagnosis, age, gender, and length of stay. Trends were examined by logistic regression analysis. Results: There were 11, 182 hospital admissions with any listed diagnosis of CF from 2009 to 2013, 36% of which were in the <14 age group (n = 3763) and 54% of whom were >14 years (n = 7419). The number of patients aged 0–14 years significantly increased annually from 659 in 2009 to 809 in 2013 (r 2 =0.8, p = 0.04). The number of admissions in the >14 year group increased numerically from 1363 in 2009 to 2184 in 2013 but this was not statistically significant (r 2 =0.6, p = 0.15). There was a significant difference between age groups requiring admission for CF with a bimodal age distribution, increasing from 10–14 year age group and again in the 20–24 year age group prior to rapidly dropping (p= <0.0001). The age of all patients admitted for CF significantly increased from 2009–13 from 24 yrs to 29 yrs (r 2 =0.9, p = 0.02). The ratio of male to female CF admissions varied by age with a bimodal distribution peaking at 10–14 years and at 25–29 (p = 0.03). CF was most frequent diagnosis <14 followed by pneumonia and LRTI. ALOS was greater for those <14 than those >14 (8 v 15, p= <0.01). From 2009–2012 46 inhospital deaths occurred in CF patients. The average annual incidence of death was 12 with a mean age of 27. Conclusion: There has been a significant annual increase in admissions among CF patients <14 years and a numerical increase in those >14 years. The need for admission varies significantly with age and gender. The ALOS is significantly shorter in those <14 years and the age of admission is significantly increasing in those >14 years. Inpatient CF age of death has not significantly improved from 2009–2012.